Datacenter Berbasis Software Defined Network Dan Edge Computing untuk Instansi Kecil Dan Menengah - Ali Ahmadi; Erwin Yulianto; Awan Setiawan (Masoem University, 2021)
Datacenters have become a necessity for institutions that require reliable and high-power internal computing services. Datacenter construction allows users unlimited access to infrastructure, applications, and other IT resources as well, Software Defined Network (SDN) allows network operators and administrators to adjust resources and bandwidth as needed, providing a datacenter with increased efficiency, flexibility, and durability. Edge Datacenter, in general, can be said to be a datacenter with minimal facilities that can expand its network access to provide cloud computing resources, and serve cached content to local end-users,because the Edge Datacenter implements edge-caching. So that to increase the flexibility and scalability of the datacenter with some problems related to location and space that is really limited, the application of SDN and Edge Computing are alternatives that need to be considered.